Batwoman. The complete second season [videorecording (DVD)]. - Rose, Ruby, 1986-; Skarsten, Rachel, 1985-; Tandy, Meagan, 1985-; Kang, Nicole (Warner Bros. Home Entertainment, 2021)
At the end of the first season, Crows Commander Kane has declared war on Batwoman, forcing everyone to choose sides. Season two kicks off with a major game-changer that will alter Gotham and The Bat Team forever. A new hero emerges from the shadows. Relatable, messy, loyal, a little goofy, Ryan Wilder couldn't be more different than the woman who wore the Batsuit before her, billionaire Kate Kane. Living in her van, Ryan has felt trapped and powerless by the system and believes the Batsuit is the key to breaking out of it. But what she'll come to discover is that it's not the suit that makes Ryan Wilder powerful. It's the woman inside of it who finds her destiny in changing Gotham City for good.